A compact ultra-wideband Wilkinson power divider based on trapezoidal and triangular-shaped resonators with harmonics suppression. (July 2019) - Zonouri, Seyed Abed; Hayati, Mohsen
Abstract: In this paper, a new scheme of the Wilkinson power divider (WPD) with miniaturized dimensions, 0.066 λg × 0.069 λg, ultra-wide stopband, i.e., 3.3–14.2 GHz, enhanced harmonic suppression, suppression of the eight harmonics, and high isolation, <‒ 15 dB, is introduced. In order to remove 2nd to 6th harmonics with a suppression level lower than −20 dB, each branch of a conventional WPD is replaced by a suppressing cell and resonators in the proposed structure, while for elimination of 7th and 8th harmonics, open stubs are employed. Moreover, even and odd mode analyses are utilized, and its relevant formulas for the electrical length and the characteristic impedance are presented. The main line between input and output signal is meandered to obtain a compact size. To generate the transmission zeros, the trapezoidal and triangular-shaped resonators are designed and utilized in the proposed structure. According to the simulation and experimental results, the center frequency of the proposed power divider is 1.65 GHz, where input and output return losses are greater than 20 dB.